Modulation of Notch signaling pathway in activated hepatic stellate cells does not ameliorate the outcome of liver fibrosis in carbon tetrachloride and DDC-feeding models - Šisl, Dino; Planinić, Pavao; Novak, Sanja; Filipović, Maša; Flegar, Darja; Šućur, Alan; Turčić, Petra; Kovačić, Nataša; Kalajzić, Ivo; Grčević, Danka; Kelava, Tomislav (Frontiers in Pharmacology, 2024)
Background: Recent research suggests a possible role of Notch signaling pathway in development of liver fibrosis, but exact cellular and molecular mechanisms are still not well defined. Methods: We modulated Notch signaling in activated hepatic stellate cells/myofibroblasts using the model of inducible activation or inhibition of Notch signaling selective for αSMA positive cells in murine models of toxic fibrosis induced by CCl4 and cholestatic fibrosis induced by DDC supplemented feeding. Results: Our results confirm that Notch signaling pathway is activated in both CCL4 and DDC model of liver fibrosis and that αSMA positive myofibroblasts are of activated hepatic stellate cells origin. However, neither the inhibition of canonical Notch signaling (in tamoxifen treated αSMACreER/RBP-Jfl/fl mice) nor its overactivation (in tamoxifen treated αSMACreER/NICD1 mice) changed the degree of liver fibrosis in comparison to the control groups in either of the investigated models. Furthermore, after the withdrawal of the fibrogenic treatment the degree of resolution of fibrosis was similar between the animals with Notch overactivation and controls. In addition to genetic manipulation, we investigated the effect of antibodies against NOTCH1 and NOTCH2 on the development of liver fibrosis. Treatment with antibodies had effects on thymus and spleen respectively, but failed to ameliorate liver fibrosis. In conclusion, our data demonstrate that modulation of Notch activity in activated HSC is not sufficient to change the outcome of liver fibrosis. The results obtained with inhibitory antibodies further demonstrate limitations of targeting Notch 1 and 2 receptors as antifibrotic therapy. Notch pathway remains a potential target for the treatment of liver fibrosis, but future studies should be directed to Notch 3 signaling and/or targeting different populations of cells.